Evidences of apoptosis during the early phases of soleus muscle atrophy in hindlimb suspended mice - ferreira, r (2008)
The purpose of this study was to investigate the occurrence and time-course of apoptosis in soleus skeletal muscle during the first 48 hours of unloading. Fifty Charles River mice were randomly divided into five groups (n = 10 each) according to the time of hindlimb suspension (HS). Mice were suspended for 0 (Control), 6 (6HS), 12 (12HS), 24 (24HS), and 48 hours (48HS). Soleus muscle atrophy was confirmed by a significant decrease of 20 % in muscle-wet weight and of 5 % in the ratio protein concentration/muscle wet-weight observed after 48 hours of unloading. The apoptotic index, the AIF (apoptosis-inducing factor) and p53 expression presented their uppermost value (304 %, 241 % and 246 %, respectively) at 24HS, and were preceded by the highest activity of caspase-3 and -8 at 12HS (170 % and 218 %, respectively) and of Bax/Bcl-2 content at 6HS (160 %). There were no marked ultrastructural alterations until 24 hours of simulated weightlessness. Lysosomal autophagic activity and infiltration of phagocytic cells were observed at 24HS and 48HS and might have contributed to the degenerative changes noticed in both groups. Though not consistently supported by morphological evidences, the biochemical parameters sustain the concept that the occurrence of apoptosis parallels the soleus atrophic response in its early phase.